Distinct metabonomic signatures of Polygoni Multiflori Radix Praeparata against glucolipid metabolic disorders. (18th March 2021) - Yang, Ya-Qin; Meng, Fan-Ying; Liu, Xin; Zhang, Mei; Gu, Wen; Yan, Hong-Li; Yu, Jie; Yang, Xing-Xin
Abstract: Objectives: Glucolipid metabolic disorders (GLMD) promote a series of major chronic diseases. Polygoni Multilori Radix Preparata (PMRP) has been widely acknowledged in the prevention and treatment of GLMD. We previously reported that water extract (WE) of PMRP and its major bioactive constituents such as polysaccharides (POL) and 2, 3, 5, 4´-tetrahydroxy-stilbene-2-O-β-D-glucoside (TSG) could alleviate GLMD. The mitochondrial dysfunction is an important mechanism of GLMD, but the underlying mechanisms behind the regulation of mitochondria to alleviate GLMD by WE, POL from PMRP and TSG are still unknown. Methods: In this study, we elucidated the effects of WE, POL, and TSG towards regulating the mitochondrial dysfunction and alleviating GLMD using mitochondrial metabonomics. A rat model of GLMD was established by high-sugar and high-fat (HS-HF) diet. Rats were intragastrically given WE, POL, and TSG for 12 weeks. The liver mitochondrial metabolites were analyzed by ultra-high-performance liquid chromatography/mass spectrometry followed by multivariate statistical analysis to identify the differential metabolites and metabolic pathways. Key findings: The WE, POL, and TSG could significantly restore the level of endogenous metabolites in liver mitochondria toward normal status. In total, sixteen, seven, and fourteen differential metabolites were identified in the liver mitochondrial samples obtained from the WE, GOL, and TSG groups, respectively. These metabolites were found to be mainly involved in glycerol phospholipid, histidine, alanine, aspartic acid, glutamate metabolism, and arginine biosynthesis. Conclusions: PMRP could improve the liver mitochondrial function by regulating the mitochondrial metabolic pathways to alleviate GLMD. Therefore, the application of PMRP might be a promising mitochondrial regulator/nutrient for alleviating GLMD-associated diseases and the mitochondrial metabonomics might provide insights into the evaluation of the efficacies and mechanisms of action of drugs.